Shedding Light on Specificity: Population Genomic Structure of a Symbiosis Between a Coral Reef Fish and Luminous Bacterium - Gould, Alison L.; Dunlap, Paul V. (Frontiers in Microbiology, 2019)
All organisms depend on symbiotic associations with bacteria for their success, yet how these interspecific interactions influence the population structure, ecology, and evolution of microbial symbionts is not well understood. Additionally, patterns of genetic variation in interacting species can reveal ecological traits that are important to gene flow and co-evolution. In this study, we define patterns of spatial and temporal genetic variation of a coral reef fish, Siphamia tubifer, and its luminous bacterial symbiont, Photobacterium mandapamensis in the Okinawa Islands, Japan. Using restriction site-associated sequencing (RAD-Seq) methods, we show that populations of the facultative light organ symbiont of S. tubifer exhibit genetic structure at fine spatial scales of tens of kilometers despite the absence of physical barriers to dispersal and in contrast to populations of the host fish. These results suggest that the host’s behavioral ecology and environmental interactions between host and symbiont help to structure symbiont populations in the region, consequently fostering the specificity of the association between host generations. Our approach also revealed several symbiont genes that were divergent between host populations, including hfq and a homolg of varS, both of which play a role in host association in Vibrio cholerae. Overall, this study highlights the important role that a host animal can play in structuring the distribution of its bacterial symbiont, particularly in highly connected marine environments, thereby promoting specificity of the symbiosis between host generations.